المشكلات النمطية للمراهقين من منظور المراهق، الولي والأستاذ - بوشارب, فوزية; زعرور, لبنى (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة الى الوقوف على المشكلات النمطية من منظور المراهق نفسه، الولي والأستاذ . أجريت على عينة قصدية قوامها 64 فردا موزعين بين29 تلميذا، 16 أستاذا و 19 ولي. انطلقنا من طرح تساؤلات: ما هي المشكلات النمطية لدى المراهقين حسب تصور كل من المراهق، الولي و الأستاذ ؟ هل هناك فروق بين تصوراتهم ؟ و هل يوجد تصور مشترك لأسباب وطرق علاج هذه المشكلات ؟ و توصلنا من خلال هذه الدراسة إلى وجود مشكلات نمطية بارزة لدى المراهقين حسب تصور كل من المراهق، الولي و الأستاذ. فكانت تصوراتهم للمشكلات النمطية بمختلف أبعادها متوسطة ما عدا المجال المدرسي فكانت تقديراتهم للمشاكل الدراسية عالية. كما كانت الفروق دالة إحصائيا بين المراهقين و الأولياء و دالة إحصائيا بين الأساتذة و المراهقين، و لا توجد فروقا دالة إحصائيا بين الأولياء و الأساتذة. أما عن أسباب وطرق علاج المشكلات البارزة لدى المراهقين للفئات الثلاث و نظرا لعدم إقبال أفراد العينة للإجابة عليها، بقيت الفرضية معلقة. Abstract : The aim of this study stood for the stereotype problems from the viewpoint of the adolescent himself, the parent’s and the teacher’s. The research conducted on an intentional sample of 64 people consisting of 29 pupils, 16 teachers and 19 parents. We started from a number of questions: what are the adolescent’s stereotype problems from the perceptions of the adolescent, the parent and the teacher? Are there any differences between their perceptions? Is there a common perception about the reasons and ways of solving those problems? We have found that there are prominent stereotype problems of the adolescents from the view point of the adolescents, parents and the teachers. Their perceptions to the stereotype problems were average except for the schooling which were high. The differences were statistically significant between the adolescents and the parents, statistically significant between the teachers and the adolescents. There haven’t been any significant statistical differences between parents and teachers. Concerning the reasons and the solutions to the prominent problems of the adolescents for the three categories, the hypothesis still pending because the sample didn’t respond to it.
مقال
Keywords: مشكلات نمطية؛ أساتذة؛ مراهقين؛ أولياء؛ منظور; Stereotype Problems; the Teachers; the Adolescents; Parents; Perception